2009
DOI: 10.4067/s0718-58392009000400010
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Dry Olive Cake Modifies Subcutaneous Fat Composition in Lambs, Noting Cake Resistance to Degradation and Peroxidation

Abstract: The purpose of this experiment was to determine the extent to which lamb carcass quality and fat composition could be altered by applying a dry olive cake-based ration instead of a conventional ration or pasture feeding. Three treatments were compared in a completely randomized experiment using 36 single male Suffolk Down lambs with an initial age and live weight of 80 d and 25 kg, respectively. The three treatments were: (a) suckling lambs kept with their mothers on annual Mediterranean grassland (GRAZE); (b)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
(40 reference statements)
5
12
0
2
Order By: Relevance
“…In the present trial, the olive cake was obtained by a three-phase extraction system coupled with a stoning system after the oil extraction. The values of NDF, ADF, ADL and CP content were higher than those found by Vera et al (2009) in stoned olive cake obtained from two-phase system, whereas ether extract was lower (Supplementary Table S1). As expected, the fattyacid composition of olive cake was high in c9-18:1 (more than 75% of total fatty acids).…”
Section: Resultsmentioning
confidence: 73%
“…In the present trial, the olive cake was obtained by a three-phase extraction system coupled with a stoning system after the oil extraction. The values of NDF, ADF, ADL and CP content were higher than those found by Vera et al (2009) in stoned olive cake obtained from two-phase system, whereas ether extract was lower (Supplementary Table S1). As expected, the fattyacid composition of olive cake was high in c9-18:1 (more than 75% of total fatty acids).…”
Section: Resultsmentioning
confidence: 73%
“…The similarity in total MUFA and C18:1n-9c contents for all groups confirmed the lack of effects of an acorn diet on MUFA in lamb meat (Keddam et al, 2010); however, these authors recorded higher contents of MUFA (45%) and C18:1n-9c (40%) than those found in our study (32 and 28% for MUFA and C18:1n-9c, respectively). Despite the similarity in FA composition of olive cake and acorns, particularly their richness in oleic acid, the C18:1 content in the subcutaneous fat of lambs receiving olive cake was higher than that in lambs receiving barley concentrate (47 and 43%, respectively; Vera et al, 2009).…”
Section: Fatty Acid Compositionmentioning
confidence: 85%
“…Thus, the present results indicate that despite its nutritional limitations, locally produced olive oil cake can make as much as one-third of the concentrate diet, replacing traditional, more expensive, and imported feeds. It is also clear that carcass yield and conformation were not altered by inclusion of cake in the ration while Vera et al (2009) reported that cake feeding improved the fatty acid profile of subcutaneous adipose tissue. Lastly, it remains to be established if consumers would perceive differences in flavour and other organoleptic properties of the meat, although an untrained panel of naïve consumers failed to differentiate meat from the different treatments (C. Aguilar, R. Vera, R. Lira, unpubl.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of a large amount of little used olive residues with the need to intensify and differentiate fat lamb production has attracted interest, and Vera et al (2009) demonstrated that supplementing lambs with olive oil cake significantly improves the fatty acid profile of subcutaneous fat and, by inference, that of other tissues as well. Thus, the objective of the present work was to compare three contrasting lamb finishing systems and determine if the incorporation of a relatively large amount of olive oil cake into lambs' rations would alter their performance relative to a conventional concentrate diet or as supplement to an annual pasture.…”
Section: Introductionmentioning
confidence: 99%